2022
DOI: 10.1002/cac2.12393
|View full text |Cite
|
Sign up to set email alerts
|

Cancer situation in China: what does the China cancer map indicate from the first national death survey to the latest cancer registration?

Abstract: Background Over the past four decades, the Chinese government has conducted three surveys on the distribution of causes of death and built cancer registration. In order to shine a new light on better cancer prevention strategies in China, we evaluated the profile of cancer mortality over the forty years and analyzed the policies that have been implemented. Methods We described spatial and temporal changes in both cancer mortality and the ranking of major cancer types in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…There are three general categories of breast cancer: hormone receptor-positive (HR+), human epidermal growth factor receptorpositive (HER2+), and triple-negative (TN). [313][314][315] Distant metastasis and therapy resistance are the root cause of the poor prognosis of the majority of patients with breast cancer. 316,317 Accumulating evidence suggests that all the STAT family members are closely associated with breast cancer, having either protumorigenic or antitumorigenic characteristics.…”
Section: The Jak-stat Pathway and Diseasesmentioning
confidence: 99%
“…There are three general categories of breast cancer: hormone receptor-positive (HR+), human epidermal growth factor receptorpositive (HER2+), and triple-negative (TN). [313][314][315] Distant metastasis and therapy resistance are the root cause of the poor prognosis of the majority of patients with breast cancer. 316,317 Accumulating evidence suggests that all the STAT family members are closely associated with breast cancer, having either protumorigenic or antitumorigenic characteristics.…”
Section: The Jak-stat Pathway and Diseasesmentioning
confidence: 99%
“…Cancer has emerged as one of the most hazardous diseases threatening human life and health globally due to its late diagnosis, ease of spread and metastasis, and susceptibility to drug resistance. Early diagnosis of cancer is crucial and remains a great challenge in modern therapeutics. Although cisplatin (CDDP) is currently the most widely used treatment for various cancers, it is unable to cure cancer in a timely and effective manner for the following reasons: (1) it cannot diagnose tumors; (2) it only acts on a single target DNA, which makes it easy to develop drug resistance for cancer cells and produces severe side effects; , and (3) it cannot effectively inhibit tumor metastasis. , Therefore, it is significant to develop next-generation anticancer metal agents to overcome the shortcomings of CDDP and more effectively cure cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the World Health Organization’s colorectal cancer epidemiological data for the whole of 2022 show that Asia ranks first in terms of colorectal cancer incidence, mortality, and 5-year prevalence (colon, rectum), followed by Europe with the second highest share[2]. Studies have shown that the incidence and mortality of CRC have decreased in some European, Oceanian and North American countries in recent years [3–5], but data from the Chinese Cancer Center in 2022 show that the incidence and mortality of CRC continue to increase [3, 67]. Worryingly, the incidence of colorectal cancer is steadily increasing in China and globally in people under the age of 50 [814].…”
Section: Introductionmentioning
confidence: 99%
“…Center in 2022 show that the incidence and mortality of CRC continue to increase [3,[6][7] . Worryingly, the incidence of colorectal cancer is steadily increasing in China and globally in people under the age of 50 [8][9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation